Análise do custo econômico do transplante renal - Conrad, Andréa Trennepohl (2014)
A kidney transplant is an expensive surgery due to the lack of donors, the use of medication for a long time and the need to perform medical procedures. One wonders, what is the cost of kidney transplantation? This research aims to analyze hospital costs of a kidney transplantation, comparing costs between living and deceased donors and evaluating the important association between costs and clinical variables. The survey was conduct in eight-one medical records from patients who underwent kidney transplantation, considering both living and deceased donors. Therefore the following steps were developed: billing, auditing and process costing. The variables analyzed were related to the recipients, donors and the kidney transplantation. For statistical analyses the linear regression method was adopted. To evaluate the kidney transplant costs and the impact of a range of variables was used the significance level of p≤ 0,050 and 95% of statistical power. The comparison of the costs between living and deceased donors revealed an average difference of $ 4,000.00. In a transplant with a living donor the costs are lower due to the fact it is an elective procedure where is possible to choose a more compatible donor while in a transplant with a decease donor the costs are higher and are related to the retarded recovery from the kidney transplant. In the first case most of the costs are owing to the hospitalization and intensive care unit (ICU) while in the second case it also presents high costs with extra procedures and medical treatment